Character strengths-based interventions: Open questions and ideas for future research. Issue 5 (2nd September 2020) - Ruch, Willibald; Niemiec, Ryan M.; McGrath, Robert E.; Gander, Fabian; Proyer, René T.
ABSTRACT: Numerous studies have confirmed the effectiveness of character strengths-based interventions for fostering well-being. However, there are still several open questions. The present article discusses some of the most important questions. We review the current body of research and provide ideas and possible future directions on issues such as: Should interventions be generic or personalized? What strengths should be addressed in a strengths-based intervention? What is the role of signature strengths? Do strengths-based interventions change the level of character strengths? How can you justify strengths-based interventions? We conclude that increasing knowledge has not tempered but rather has heightened the initial high expectations on the important contribution of strengths-based interventions in research and practice, but still much work remains to be done.